Conceptualising the moderating role of knowledge management within supply chain risks and supply chain risk management - Waqas, Umair; Abd. Rahman, Azmawani; Ismail, Normaz Wana; Kamal Basha, Norazlyn; Umair, Sonia (Universitas Hasanuddin, 2019)
There is a dearth of empirical and theoretical investigation in the field of supply chain risk management. Even though SCRM is an important component in supply chain management research, there is still a lack of understanding regarding the term and the concept to develop advantageous SCRM. In the literature of SCRM, different aspects have been discussed, for instance, risk identification, risk assessment, risk management strategies, risk monitoring, and contingency plans. Supply chain risks are increasing because of multiple outsourced partners linked with each other making it more complex, along with this, business is also uncertain, so these scenarios increase supply chain risks. Knowledge management has been used to know about the market scenarios and the information of trading partners and supply chain managers from different firms to know about the uncertainty or risks. However, the discussion shows that the efficient implication of KM capabilities on the SCRs and SCRM is still lacking. This paper provides a comprehensive conceptual framework on the effect of knowledge management within supply chain risk and supply chain risk management.